The effect of artificial intelligence (AI) intensity on students satisfaction in completing college assignments - Siswahyuningsih, Zahrotunnisa; Mahfudhoh, Aini (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
The rapid development of AI is influenced by the intensity of its use and the benefits felt by its users. The widespread use of AI without a foundation in literacy and the buying and selling of AI prompts have weakened critical thinking skills. This phenomenon has sparked interest in researching the intensity of AI use among college students. This study aims to analyze the effect of AI usage intensity on college student satisfaction in completing college assignments. This quantitative research uses an explanatory associative research method with simple linear regression analysis to test the independent variable (AI usage intensity) and the dependent variable (usage satisfaction). Data collection was conducted via an online questionnaire On Google Forms for master's students in the Islamic Education Management study program in Tulungagung Regency, with a total of 60 respondents. The results showed a linear relationship between the intensity of AI use and college student satisfaction with completing college assignments. The findings indicated that a one-unit increase in AI use intensity would increase student satisfaction by 0.466 units. The effect of AI usage intensity, as measured by the coefficient of determination, is 26.9% on student satisfaction with completing course assignments. This study concludes that the intensity of AI usage among college students must be regulated immediately so that satisfaction in completing course assignments is accompanied by academic competence and ethics.